Revisiting Drymaeus germaini (Ancey, 1892) (Gastropoda, Bulimulidae): ecological niche and first anatomical description of a poorly known land snail species from Brazil - Maria Isabel Pinto Ferreira Macedo; Ximena Maria Constanza Ovando; Sthefane D’ávila (PeerJ)
Background Terrestrial gastropods are one of the most imperiled animal groups in the world. However, information on population size and structure, geographic range and their trends over time, which is necessary to assess species conservation status, is unavailable or insufficient for most land snail taxa, making it difficult to apply the IUCN criteria. Ecological niche modelling (ENM) has been used to predict geographic distribution, allowing better characterization of the distribution ranges of endemic or rare species, offering the necessary information for stating their conservation status and planning for conservation measures. Methods We compiled occurrence records of Drymaeus germaini and D. suprapunctatus (herein proposed as a junior synonym of D. germaini) associated with museum collections and human observation. A distribution map including geographic boundaries and Brazilian biomes was made with QGis version 3.10.14. For niche modelling, seven bioclimatic variables were used as predictors. The models were performed using different packages in R environment version 4.2.0. Results and Discussion We have redescribed Drymaeus germaini based on the inner anatomy and shell sculpture, also providing the first comparative conchological analysis with congeneric species. We also updated the current distribution of the species within the main Brazilian biomes and estimated its potential geographic distribution using the ENM approach. The ENM results revealed a belt of mid-to-high suitability areas from Northeast to South Brazil in the Atlantic Forest, the most degraded biome in Brazil. In the Northeast these areas extended from the Atlantic Forest to the Caatinga and in the South, from the Atlantic Forest to the Pampas. Additional areas of mid-suitability were found in Cerrado, the second most degraded biome in Brazil. Our results also revealed a continuous area of mid-to-high environmental suitability for D. germaini within the Arc of Amazon deforestation. Our results evidence the scarcity of occurrence records for this species and most of these records do not correspond to protected areas. Also the ecologically suitable areas for D. germaini are in regions disturbed by deforestation, fires, urbanization, habitat loss, mining, and flooding, which may represent the main threats for this species. Nonetheless, the information necessary to apply the IUCN criteria for D. germaini is still incipient and this species should be classified as data deficient.